The nature of restorative processes in the testеs of rats at different periods after cessation of alcohol abuse - Грицуляк, Б. В.; Грицуляк, В. Б.; Пастух, М. Б.; Івасюк, І. Й.; Долинко, Н. П. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Histological and ultrastructural changes in testes among 27 laboratory rats at different periods after termination of ethanol administration have been studied. It has been established that recovery processes in convoluted seminiferous tubules of testes are observed in terms of the two-week experiment and significant increase in the number of developing germ cells has been shown. Increase of alcohol abuse up to 3 weeks dramatically reduces recovery processes in convoluted seminiferous tubules. Marked decrease of spermatotsyts and spermatids number and volume of interstitial nuclei endocrinocytes has been revealed.